Design thinking in integrated STEAM learning: Surveying the landscape and exploring exemplars in elementary grades. (27th February 2018) - Cook, Kristin L.; Bush, Sarah B.
Abstract: Complementing the aims of problem‐based inquiry, a pedagogical approach called design thinking (DT) has students grapple with issues that require a creative redefinition and reimagining of solutions akin to professional skills of designers, who consider conflicting priorities and complex negotiations to arrive at a solution to an ill‐defined problem. This article aims to synthesize the limited existing literature on the use of DT in the K–12 classroom, share two exemplars of DT in action in Grades 3–5 so that science, technology, engineering, arts, and mathematics (STEAM) educators, teacher educators, researchers, and other stakeholders can visualize how it can take shape in the elementary classroom, followed by concluding remarks on DT. The DT framework provides an exciting avenue for teaching more than simply the content areas of STEAM, it provides a vehicle through which a true transdisciplinary learning experience can occur—where students are passionately invested in solving problems as they strive to make the world a better place.